Appendiceal disease in hematopoietic cell transplantation. Issue 2 (3rd February 2022) - Wright, Zachary; Essien, Francis; Renshaw, John; Wiggins, Michael; Brown, Alexander; Osswald, Michael
Abstract: Appendiceal diseases are rare reported complications during hematopoietic stem cell transplantation with no guidance on management in the published literature. Medical therapy may be considered in selected patients prior to surgical solutions. Abstract : Appendiceal diseases are rare reported complications during hematopoietic stem cell transplantation with no guidance on management in the published literature. Medical therapy may be considered in selected patients prior to surgical solutions.